Laminated Polymer Solar Cells with PEDOT：PSS Film as Anode - 侯腾 梁春军 张福俊 何志群 孙凯 (Chinese physics letters, 2014)
A prefabricated conductive polymer film of polymer poly（3,4-ethylenedioxy-thiophene）：poly （styrene-sulfonate） （PEDOT：PSS） is developed and is used as the anode in an inverted polymer solar cell （PSC） through a lamination process. The geometry structure of the PSC is indium tin oxide/interface layer/P3HT：PCBM/PEDOT：PSS. The PEDOT：PSS electrode is 5 μm and the sheet resistance is 10Ω/sq. The device fabrication process is vacuum-free and extremely simple. Lithium carbonate （Li2CO3） and cesium carbonate （Cs2C03） are used as the cathode interface layers, respectively, and the result shows that Li2CO3 can enhance the open-circuit voltage （Voc） and fill factor distinctly, and the power conversion efficiency （PCE） can reach 2.1%.